2023
DOI: 10.1111/head.14526
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility spectrum disorders and active migraine in Israeli adolescents: A nationwide study

Abstract: Objective: To assess the association between hypermobility spectrum disorders/hypermobile type Ehlers Danlos Syndrome (HSD/hEDS) and migraine in a national sample of adolescents in Israel. Background:The association between HSD/hEDS and migraine is unclear, even more so in pediatric populations.Methods: This population-based, cross-sectional study included 1,627,345 Israeli adolescents (945,519/1,626,407 [58%] males; mean age 17 ± 0.5 years) who were medically assessed before mandatory military service during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…If migraine was reported in the medical records provided by the primary physician or a history of frequent headaches in the past year was elicited during the medical interview, the adolescent was referred to a neurologist. All migraine diagnoses were confirmed by board-certified neurologists according to the International Classification of Headache Disorders (11), as previously described (12). Adolescents who were diagnosed with migraine and experienced at least one migraine attack per month in the past year were assigned a diagnostic code that indicated active migraine.…”
Section: Methodsmentioning
confidence: 99%
“…If migraine was reported in the medical records provided by the primary physician or a history of frequent headaches in the past year was elicited during the medical interview, the adolescent was referred to a neurologist. All migraine diagnoses were confirmed by board-certified neurologists according to the International Classification of Headache Disorders (11), as previously described (12). Adolescents who were diagnosed with migraine and experienced at least one migraine attack per month in the past year were assigned a diagnostic code that indicated active migraine.…”
Section: Methodsmentioning
confidence: 99%
“…to provide precise therapeutic approaches, including medication treatments and non-pharmacological options incorporating lifestyle modifications that target the shared pathophysiology between migraine and HSD/hEDS. Finally, the study also demonstrated how leveraging established large nationwide datasets can provide important insights into the link between diseases and points to future research directions.In summary, Zloof et al3 reported an important observation of the association between migraine and HSD/hEDS among adolescents utilizing a large nationwide dataset. Future research directions include deciphering the underlying pathophysiology of both conditions, and the development of specific treatment strategies tailored to patients affected by both conditions.…”
mentioning
confidence: 97%
“…1,2 In clinical practice, it is not uncommon to see patients severely affected by both migraine and HSD/hEDS, and the management can sometimes be challenging given the multitude of symptoms involved in this population. The recent study "Hypermobility Spectrum Disorders and Migraine in Adolescents-A Nationwide Study" conducted by Zloof et al 3 and published in Headache, is an important study that reported the association between (HSD/hEDS) and migraine in adolescents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status was reported by residence locality at the time of examination. 5 Sociodemographic differences between adolescents with hyperhidrosis and the control group were evaluated using 2-sample, 2-tailed t tests (continuous variables) and χ 2 tests (categorical variables). Logistic regression models were used to calculate the odds ratio (OR) and 95% CIs for HSD or hEDS with or without hyperhidrosis.…”
mentioning
confidence: 99%